Scorpion. Season two [videorecording (DVD)] - Santora, Nick, 1970- (CBS DVD, 2016)
The new Director of Homeland Security reunites the team when a nuclear powered Russian satellite is knocked out of orbit and must be diverted before it detonates over Southern California. The team races against time to stop an unstable ex-member of Scorpion, Mark Collins who kidnaps and threatens to kill Toby if his demands are not met.